Flocculation Performance of Industrial Sugarcane Juice by Acrylamide-Based Anionic Flocculant - Eva Oktavia Ningrum; Agung Subyakto; Wirawan Ciptonugroho; Shania Lorensa; Devianti Anggraini Ramadhani; Agus Surono (Indonesian Journal of Chemistry, 2023)
Despite the widespread use of ionic polymer flocculants in sugar refineries, there is still insufficient knowledge on the relationship between the polymer properties and the efficiency of flocculation. This paper describes the performance of poly(sodium acrylate-co-acrylamide) (poly(SA-co-AAm)) as an anionic flocculant in the flocculation–coagulation of sugarcane juice from the sugar factory Gempolkrep PTPN X Mojokerto. Poly(SA-co-AAm) was successfully prepared via free radical polymerization of sodium acrylate and acrylamide with respective molar ratios of 40:60, 50:50, and 60:40, and compared with the commercial flocculant Accofloc. It was found that the mud height of the sugarcane decreased with increasing SA:AAm ratio. However, mud height increase was observed with further increasing SA:AAm ratio. Furthermore, increasing the flocculant dosage did not induce any significant change in the mud height and pH. The total dissolved solids (TDS) significantly decreased when the ratio of sodium acrylate:acrylamide was changed from 40:60 to 50:50, whereas a further change to 60:40 increased the TDS value again. It is also noticed that the tendency of turbidity is consistent with the TDS value. These results demonstrate that poly(SA-co-AAm) is a feasible alternative to the commercial flocculant owing to its good flocculation–coagulation performance with an optimum SA:AAm ratio of 50:50.